Assessment of the current spatial-temporal variations of salinity on the surface waters of Kuala Perlis, Perlis / Aimie Rifhan Hashim ... [et al.] - Hashim, Aimie Rifhan; Kamaruddin, Sharir Aizat; Abd.Aziz, Khairul Naim; Tajam, Jamil; Buyong, Faeiza; Che Ismail, Che-Zulkifli; Lee Abdullah, Anisah; Azis, Tun Mohd Firdaus; Anscelly, Anastacia (Faculty of Applied Sciences, 2023)
Tropical estuaries are known for their diverse hydrological features and rich biodiversity, significantly impacting various species. However, changes in salinity exposure gradients can cause continuous modifications in estuaries' physicochemical properties and habitats. This study aimed to assess the spatiotemporal variations in salinity levels in the surface water of Kuala Perlis, Perlis. In December 2021, five sampling stations were established for each morning, afternoon, and evening session, and salinity values were measured using a refractometer. Analysis of Variance was conducted at a significance level of 0.05 to determine the differences in the spatiotemporal distribution of salinity values using Statistical Package for Social Sciences (SPSS) version 26. The results showed three different salinity ranges along the Sungai Kuala Perlis, ranging from 0.41 to 5.00 ppt, 0.79 to 24.74 ppt, and 0.33 to 14.00 ppt for the morning, afternoon, and evening periods. The salinity ranges varied between the different sampling times. Still, no statistically significant difference was found in the salinity values concerning spatial and temporal variations (> .05). These findings provide preliminary data for river monitoring by authorities, non- governmental organizations, and researchers, as salinity significantly affects water quality conditions in estuaries, particularly the amount of dissolved oxygen.